Prophylactic tamsulosin can reduce the risk of urinary retention after surgery in male patients: A systematic review and meta-analysis - Li, Hua; Zhang, Wupeng; Xu, Gaoxiang; Wang, Daofeng; Xu, Cheng; Zhang, Hao; Zhang, Licheng; Li, Jiantao; Tang, Peifu (Frontiers in Surgery, 2022)
Objective The meta-analysis aimed to estimate the efficacy of prophylactic tamsulosin on postoperative urinary retention (POUR) in male patients. Methods Papers were searched in the PubMed, Embase, Web of Science and Cochrane Library databases with predetermined keywords up to March 1st 2022. The studies reporting the preventive efficacy of prophylactic tamsulosin on POUR among men were identified. Pooled risk ratios (RRs) were calculated based on the random-effects model. Meta regression was performed to explore potential sources of heterogeneity. Results There were 11 studies with 1046 patients in the Tamsulosin group and 1113 patients in the Control group. The risk of POUR was significantly lower in the Tamsulosin group (123/1046 [11.8%] VS 238/1119 [19.0%]; RR = 0.61; 95% confidence interval [CI] 0.43 to 0.87; P = 0.006; Heterogeneity: I2 = 57%; P = 0.009). Administration of tamsulosin was related to higher risk of adverse events (57/688 [8.3%] VS 33/624 [5.3%]; RR = 1.68; 95% CI 1.13 to 2.48; P = 0.010; Heterogeneity: I2 = 33%; P = 0.20). The level of evidence and mean age of the included patients were identified as the potential sources of heterogeneity. Conclusion The present meta-analysis indicated that prophylactic tamsulosin helps in preventing POUR and younger patients might benefit more from this preventive regimen. Administrating tamsulosin was also associated with a possibly higher risk of adverse events.